Mucosal Tuft Cell Density Is Increased in Diarrhea-Predominant Irritable Bowel Syndrome Colonic Biopsies - Aigbologa, Jessica; Connolly, Maeve; Buckley, Julliette M.; O'Malley, Dervla (Frontiers in Psychiatry, 2020)
Tuft cells are rare chemosensory sentinels found in the gut epithelium. When triggered by helminth infection, tuft cells secrete interleukin-25 (IL-25) basolaterally and subsequently evoke an immune response. Irritable bowel syndrome (IBS) is a common and heterogeneous disorder characterised by bowel dysfunction and visceral pain sensitivity. Dysfunctional gut-brain communication and immune activation contribute to the pathophysiology of this disorder. The study aims were to investigate changes in tuft cell density in non post-infectious IBS patients. Immunofluorescent labelling of DCLK1-positive tuft cells was carried out in mucosal biopsies from the distal colons of diarrhoea and constipation-predominant IBS patients and healthy controls. Tuft cell numbers were also assessed in animal models. Concentrations of interleukin-25 (IL-25) secreted from colonic biopsies and in plasma samples was analysed using an immunoassay. The density of tuft cells was increased in diarrhoea- but not constipation-predominant IBS patient colonic biopsies. Biopsy secretions and plasma concentrations of IL-25 were elevated in diarrhoea- but not constipation-predominant IBS participants. Tuft cell hyperplasia was detected in a rat model of IBS but not in mice exposed to chronic stress. Tuft cell hyperplasia is an innate immune response to helminth exposure. However, the patients with diarrhoea-predominant IBS have not reported any incidents of enteric infection. Moreover, rats exhibiting IBS-like symptoms displayed increased tuft cell density but were not exposed to helminths. Our findings suggest that factors other than helminth exposure or chronic stress lead to tuft cell hyperplasia in IBS colonic biopsies.